Tackling Ambulatory Safety Risks Through Patient Engagement: What 10, 000 Patients and Families Say About Safety-Related Knowledge, Behaviors, and Attitudes After Reading Visit Notes. Issue 8 (18th December 2021) - Bell, Sigall K.; Folcarelli, Patricia; Fossa, Alan; Gerard, Macda; Harper, Marvin; Leveille, Suzanne; Moore, Caroline; Sands, Kenneth E.; Sarnoff Lee, Barbara; Walker, Jan; Bourgeois, Fabienne
Abstract : Supplemental digital content is available in the text. Abstract : Background: Ambulatory safety risks including delayed diagnoses or missed abnormal test results are difficult for clinicians to see, because they often occur in the space between visits. Experts advocate greater patient engagement to improve safety, but strategies are limited. Patient access to clinical notes ("OpenNotes") may help close the safety gap between visits. Methods: We surveyed patients and families who logged on to the patient portal and had at least one ambulatory note available in the past 12 months at two academic hospitals during June to September 2016, focusing on patient-reported effects of OpenNotes on safety knowledge, behaviors, and attitudes. Results: A total of 6913 (28%) of 24, 722 patients at an adult hospital and 3672 (17%) of 21, 579 participants at the children's hospital submitted surveys. Approximately 75% of patients and parents each reported that reading notes helped them understand the reason for both tests and referrals, and approximately 50% felt that it helped them complete tests and referrals. Roughly 75% of participants were more likely to check and understand test results. Overall, 97% of participants reported that trust in the provider, activation, patient-provider goal alignment, and teamwork were each better or the same after reading 1 note or more. Nonwhite participants and those with high school education or less were 30% to 50% more likely to report that reading notes helped them complete tests compared with white and more educated respondents, respectively. Conclusions: Overall, the majority of more than 10, 000 patients and parents reported reading notes helped them understand and follow through on tests and referrals. As information transparency spreads, OpenNotes can help activate patients and families, facilitate safety behaviors, and forge stronger partnerships with clinicians.